Effect of initial water content on soil failure mechanism of loess mudflow disasters - Yang, Zhiquan; Chen, Mao; Zhang, Jie; Ding, Pan; He, Na; Yang, Yi (Frontiers in Ecology and Evolution, 2023)
The frequency of mudflow disasters induced by rainfall in the Loess Plateau is increasing with the occurrence of global warming. The initial soil water content is one of the basic properties of soil, which affects the initiation of loess mudflow. In this work, a field study of the debris flow gullies in Yan'an City, Shaanxi Province, China, was conducted, and the main factors that induce gully loess mudflow were summarized. Based on the investigation results, a flume model was designed to carry out flume experiments with different initial soil water contents. The experimental results demonstrate the following. (1) Different initial soil water contents lead to different soil failure models. The damage of soil by water flow when the soil water content is in the range of 0%-5% is mainly gully erosion; that within the range of 10%-15% is mainly rill surface erosion; that within the range of 20%-25% is mainly dam breach failure. (2) When the water content of loess is equal to or less than 5% or equal to or greater than 20%, soil can promote the formation of loess mudflow, and the destruction of soil is more likely to cause mudflow disasters. In contrast, when the moisture content is within 10%-15%, loess mudflow is not easily produced. The research results of the initial water content provide not only theoretical support for the study of loess mudflow disasters in the Loess Plateau, but also a reference for the prevention and control of loess mudflow disasters in this area.